Studies on the binding and interaction of neolactotetraosylceramide and peptides with dengue virus type 2 envelope protein / Asfarina Amir Hassan - Asfarina, Amir Hassan (2019)
Dengue fever is a common tropical infection and this acute febrile illness can be a deadly infection in cases of severe manifestation, causing dengue haemorrhagic shock syndrome. Due to the nature of the mosquito-borne infection, dengue has become a significant public health threat in many developing tropical countries. In this study, envelope (E) protein is selected as a target for drug design because it is believed to be responsible for the initial viral attachment to target cells and for mediating cellular entry of the virus. Domain III of the E-protein is found to be critical for virus adsorption to the receptors expressed on the host cell surface. In the present work, the ability of potential inhibitors to inhibit DENV was assessed in silico through docking of ligands into the 1OKE pdb structure, followed by binding modes analysis and calculations of the free energy of binding. The ligands involved were neolactotetraosylceramide (nLc4Cer) and peptides (19-28 amino acids) that were believed to inhibit the trimeric conformation formation of DENV E-protein. The E-protein-nLc4Cer and peptide Eprotein complex models were generated using AutoDock 4.2 and Swarmdock docking programs. Then, the interaction of complexes were analysed using molecular dynamics simulation, followed by evaluation of the binding free energy and per-residue free energy decomposition analysis using the Molecular Mechanics Poisson Boltzmann Surface Area (MMPBSA) and Molecular Mechanics Generalized Born Surface Area (MMGBSA). The amino acid residues in the DENV E-protein important for the interactions with inhibitors had also been highlighted. These computational studies suggest that nLc4Cer and the peptides involved are proposed as potential inhibitors of DENV E-protein and are feasible to be developed as antiviral drugs for the treatment of iv dengue fever. The information gathered may pave the way for the design of new antidengue drugs thereby aiding the discovery of a therapeutic cure for this infectious disease. Keywords: dengue, peptide, envelope protein, molecular dynamics simulation, free energy of binding